Further pharmacological characterization of 5-HT(2C) receptor agonist-induced inhibition of 5-HT neuronal activity in the dorsal raphe nucleus in vivo. - Quérée, P; Peters, S; Sharp, T (2009)
BACKGROUND AND PURPOSE: Recent experiments using non-selective 5-hydroxytryptamine (5-HT)(2C) receptor agonists including WAY 161503 suggested that midbrain 5-HT neurones are under the inhibitory control of 5-HT(2C) receptors, acting via neighbouring gamma-aminobutyric acid (GABA) neurones. The present study extended this pharmacological characterization by comparing the actions of WAY 161503 with the 5-HT(2C) receptor agonists, Ro 60-0275 and 1-(3-chlorophenyl) piperazine (mCPP), as well as the non-selective 5-HT agonist lysergic acid diethylamide (LSD) and the 5-HT releasing agent 3,4-methylenedioxymethamphetamine (MDMA). EXPERIMENTAL APPROACH: 5-HT neuronal activity was measured in the dorsal raphe nucleus (DRN) using extracellular recordings in anaesthetized rats. The activity of DRN GABA neurones was assessed using double-label immunohistochemical measurements of Fos and glutamate decarboxylase (GAD). KEY RESULTS: Ro 60-0175, like WAY 161503, inhibited 5-HT neurone firing, and the 5-HT(2C) antagonist SB 242084 reversed this effect. mCPP also inhibited 5-HT neurone firing ( approximately 60% neurones) in a SB 242084-reversible manner. LSD inhibited 5-HT neurone firing; however, this effect was not altered by either SB 242084 or the 5-HT(2A/C) receptor antagonist ritanserin but was reversed by the 5-HT(1A) receptor antagonist WAY 100635. Similarly, MDMA inhibited 5-HT neurone firing in a manner reversible by WAY 100635, but not SB 242084 or ritanserin. Finally, both Ro 60-0275 and mCPP, like WAY 161503, increased Fos expression in GAD-positive DRN neurones. CONCLUSIONS AND IMPLICATIONS: These data strengthen the hypothesis that midbrain 5-HT neurones are under the inhibitory control of 5-HT(2C) receptors, and suggest that the 5-HT(2C) agonists Ro 60-0175, mCPP and WAY 161503, but not LSD or MDMA, are useful probes of the mechanism(s) involved.